The handbook of conversation analysis - Sidnell, Jack; Stivers, Tanya (Blackwell handbooks in linguistics, 2014)
Presenting a comprehensive, state-of-the-art overview of theoretical and descriptive research in the field, this book brings together contributions by leading international experts to provide an invaluable information resource and reference for scholars of social interaction across the areas of conversation analysis, discourse analysis, linguistic anthropology, interpersonal communication, discursive psychology and sociolinguistics. It is an ideal as an introduction to the field for upper level undergraduates and as an in-depth review of the latest developments for graduate level students and established scholars. It includes five sections outline the history and theory, methods, fundamental concepts, and core contexts in the study of conversation, as well as topics central to conversation analysis.